Impaired mitochondrial dynamics and abnormal interaction of amyloid beta with mitochondrial protein Drp1 in neurons from patients with Alzheimer's disease: implications for neuronal damage - Manczak, Maria; Calkins, Marcus J.; Reddy, P. Hemachandra (Human molecular genetics, 2011)
The purpose of our study was to better understand the relationship between mitochondrial structural proteins, particularly dynamin-related protein 1 (Drp1) and amyloid beta (Aβ) in the progression of Alzheimer's disease (AD). Using qRT-PCR and immunoblotting analyses, we measured mRNA and protein levels of mitochondrial structural genes in the frontal cortex of patients with early, definite and severe AD and in control subjects. We also characterized monomeric and oligomeric forms of Aβ in these patients. Using immunoprecipitation/immunoblotting analysis, we investigated the interaction between Aβ and Drp1. Using immunofluorescence analysis, we determined the localization of Drp1 and intraneuronal and oligomeric Aβ in the AD brains and primary hippocampal neurons from Aβ precursor protein (AβPP) transgenic mice. We found increased expression of the mitochondrial fission genes Drp1 and Fis1 (fission 1) and decreased expression of the mitochondrial fusion genes Mfn1 (mitofusin 1), Mfn2 (mitofusin 2), Opa1 (optic atrophy 1) and Tomm40. The matrix gene CypD was up-regulated in AD patients. Results from our qRT-PCR and immunoblotting analyses suggest that abnormal mitochondrial dynamics increase as AD progresses. Immunofluorescence analysis of the Drp1 antibody and the Aβ antibodies 6E10 and A11 revealed the colocalization of Drp1 and Aβ. Drp1 immunoprecipitation/immunoblotting analysis of Aβ antibodies 6E10 and A11 revealed that Drp1 interacts with Aβ monomers and oligomers in AD patients, and these abnormal interactions are increased with disease progression. Primary neurons that were found with accumulated oligomeric Aβ had lost branches and were degenerated, indicating that oligomeric Aβ may cause neuronal degeneration. These findings suggest that in patients with AD, increased production of Aβ and the interaction of Aβ with Drp1 are crucial factors in mitochondrial fragmentation, abnormal mitochondrial dynamics and synaptic damage. Inhibiting, these abnormal interactions may be a therapeutic strategy to reduce mitochondrial fragmentation, neuronal and synaptic damage and cognitive decline in patients with AD.